General non-specific metabolic, neuroendocrine and immune reactions to various water-salt loads in female rats - Yuriy V Zavidnyuk; Igor R Mysula; Ivan M Klishch; Walery Zukow; Igor L Popovych; Mykhaylo M Korda (Kazimierz Wielki University, 2018)
Background. This article begins with a series of articles on the effects on parameters of water-salt, nitrous and lipid metabolism, as well as the neuroendocrine-immune complex of mineral water, extracted from the bore located in the city Gertsa (Bukovyna, Ukraine). The chemical analysis prompted us to use waters Sophiya and Naftussya from spa Truskavets' as a reference as well as an artificial salt analogue of Gertsa water, which contains no organic matter or trace elements. Materials and methods. Experiment was performed on 58 healthy female Wistar rats 240-290 g divided into 6 groups. Animals of the first group remained intact, using tap water from drinking ad libitum. Instead, the other rats received the same tap water as well as waters Sophiya, Naftussya, Gertsa and its artificial salt analogue through the probe at a dose of 1,5 mL/100 g of body mass for 6 days. The day after the completion of the drinking course in all rats the parameters of metabolism and neuroendocrine-immune complex were registered. Results. Screening registered parameters found 42 among them who in rats subjected to water-salt loads, significantly different from that of intact rats, but on average the same group of animals that received liquids with different mineralization and chemical composition. Conclusion. Takes place nonspecific (general) reaction neuroendocrine-immune complex and metabolism in water-salt load as such, regardless of the specific chemical composition of fluids applied.